Efek Perendaman Air Jeruk Nipis dan Air Jeruk Lemon pada Kekasaran Permukaan Semen Ionomer Kaca - Rosalina Tjandrawinata; Andreas Julianto (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
The surface of Glass Ionomer Cement (GIC) restoration changes because of mastication forces, shear force, other functional forces, and also tooth brushing process. Things that can also change the surface of GIC restoration is kind of food and beverage consumption, such as in Indonesia, lime and lemon juice are usual beverage, and mixed in food. The purpose of this study is to determine the changes in surface roughness of GIC restoration due to lime and lemon juice immersion. Three groups GIC sample, each of ten samples were 5 mm in diameter and 2.5 mm in height. Group 1 was immersed in mineral water (as control) for 10 days. In 10 days, Group 2 was immersed in lime juice, each day 9 times @ 15 minutes and brushed with soft toothbrush for 9 times @ 3 minutes. Similar way with group 2, 10 samples of group 3 was immersed in lemon juice. Samples immersed in mineral water show changes in surface roughness of 0.977+0.503 μm, while samples immersed in lime juice show 4.267+1.489 μm, and samples immersed in lemon juice show 4.293+1.311 μm. One way ANOVA test shows significant differences among the samples (p<0.05). Post hoc Tukey test shows significant difference (p<0.05) between group 1 and group 2 and between group 1 and group 3. However, there is no significant difference between group 2 and group 3 (p>0.05). Conclusion, lime juice and lemon juice cause changes in the surface roughness of GIC more than mineral water.